ANALYSIS ETHICS AND INTEGRITY SHORT MESSAGE: CASE STUDY OF STUDENTS AT BANGKA BELITUNG UNIVERSITY - Aruna Asista; Lasmi Hartati (JURNAL KONFIKS, 2026)
The use of WhatsApp messaging can lead to violations of language ethics and a lack of awareness of the values of good and responsible communication. To establish effective communication, students must understand and apply ethics and integrity when sending text messages, especially among students at Bangka Belitung University. This study aims to describe and analyze ethics and integrity in communication, especially among students. This study also uses a qualitative approach with a case study method of Bangka Belitung University students. The research method is descriptive qualitative with a case study approach. The main data source in this study was 40 randomly selected students from the class of 2023. Meanwhile, the analysis technique was carried out using data triangulation, namely using various data sources such as observations, questionnaires, case studies, and Focus Group Discussions (FGDs) to strengthen the findings. The results show that communication ethics in text messages include choosing the right time, using opening and closing greetings, conveying one's identity, and using formal, concise, clear language that conforms to the Enhanced Spelling System (EYD). Applying these principles, including rereading messages before sending, can help students build polite, effective, and professional communication with lecturers. The conclusion of this study is that the application of ethics and integrity in communication can contribute to the creation of a more harmonious and professional academic environment not only for students but also for various other interests.